Droneducation: Empowering tomorrow's workforce through IR4.0-based curriculum - Abdul Ghani, Annisa Ummihusna; Hussain, Afifuddin Husairi; Wahi, Wahiza; Eni, Sabariah; Mohamed Sultan, Al Amin (Human Resource Management Academic Research Society, 2024)
With more jobs being taken over by digital technologies, the major concern of higher education institutes (HEIs) today is to find possible means how to develop future-ready workforces. This study explores the use of drones to enhance university students' knowledge and application within the context of Industrial Revolution 4.0 (IR4.0) education. This research's salient findings are that the students' motivation to enrol in this course is due to their interests, curiosity, and career potential, which entailed a flexible learning process beyond traditional classroom activities. Apart from that, the important synergy between universities and industries was observed to empower students' learning experience. Given the uncertainties ahead, the findings will contribute to HEIs to prepare tomorrow's workforce to meet the IR4.0 challenges.